Shifts in bacterioplankton community structure between dry and wet seasons in a tropical estuary strongly affected by riverine discharge - Marín-Vindas, Carolina (2023)
Estuaries are among the most productive ecosystems in the world and are highly dynamic due to the interaction of freshwater and seawater, which results in strong spatial gradients in physico-chemical conditions. Bacterioplankton play a central role in these systems, driving the fluxes of carbon and energy, and being central for contaminant removal in human-impacted areas. Most studies on bacterioplankton dynamics have been carried out in temperate estuaries, and they show that salinity is a major factor driving bacterioplankton distribution. Tropical estuaries, although largely understudied, experience drastic variations in river discharge between the dry and the rainy seasons, influencing the spatial distribution of the salinity gradient and thus likely impacting bacterioplankton communities. Using Illumina sequencing of the 16S rRNA gene, here we studied bacterial communities from the Nicoya’s Gulf (Costa Rica), a large tropical estuary characterized by high riverine discharge during the rainy season, to explore seasonal changes in the spatial distribution and connectivity of these communities along the Gulf. Our results show pronounced differences in bacterial diversity and community structure between seasons and zones within the estuary (the shallow upper Gulf, the middle zone and the lower zone, located in the marine end of the estuary). Bacterial communities from the different regions were more similar during the rainy season, suggesting a larger degree of microbial connectivity likely driven by the fast water circulation fueled by the riverine discharge. In the dry season, Enterobacteriales and Cyanobacteria dominated bacterial communities, whereas in the rainy season Alphaproteobacteria was the dominant group. These contrasting seasonal trends were consistent with the seasonal variations observed in bacterial assemblages during a year at a single station in the upper region of the Gulf. We conclude that the Gulf is highly dynamic in both the spatial and temporal scale and that bacterioplankton communities are strongly influenced by the riverine and tidal inputs during both seasons. This study sheds light on the sources of variability in the structure of bacterial communities in tropical estuarine systems, an understudied type of aquatic ecosystem, and sets the basis to design further comprehensive studies on their microbial diversity.